Randomized Trial of Radiation Therapy With Weekly Cisplatin or Cetuximab in Low-Risk HPV-Associated Oropharyngeal Cancer (TROG 12.01) – A Trans-Tasman Radiation Oncology Group Study - Rischin, Danny; King, Madeleine; Kenny, Lizbeth; Porceddu, Sandro; Wratten, Christopher; Macann, Andrew; Jackson, James E.; Bressel, Mathias; Herschtal, Alan; Fisher, Richard; Fua, Tsien; Lin, Charles; et al. (International journal of radiation oncology, biology, physics, 2021)
The excellent prognosis of patients with low-risk human papillomavirus (HPV)- associated oropharyngeal squamous cell carcinoma has led to concerns about overtreatment and excessive toxicity with radiation therapy and cisplatin, leading to interest in de-intensification trials. We investigated whether cetuximab, an epidermal growth factor receptor targeting antibody, when combined with radiation therapy would result in a decrease in symptom burden and toxicity with similar efficacy compared with weekly cisplatin. TROG12.01, a randomized, multicenter trial involving 15 sites in Australia and New Zealand enrolled patients with HPV-associated oropharyngeal squamous cell carcinoma, American Joint Committee on Cancer 7th edition stage III (excluding T1-2N1) or stage IV (excluding T4 and/or N3 and/or N2b-c if smoking history >10 pack years and/or distant metastases). Patients were randomized (1:1) to receive radiation therapy (70 Gy in 35 fractions) with either weekly cisplatin, 7 doses of 40 mg/m2, or cetuximab, loading dose of 400 mg/m2 followed by 7 weekly doses of 250 mg/m2. The primary outcome was symptom severity assessed by the MD Anderson Symptom Inventory Head and Neck Symptom Severity Scale from baseline to 13 weeks postcompletion of radiation therapy using the area under the curve. Trial was registered on ClinicalTrials.gov: NCT01855451. Between June 17, 2013, and June 7, 2018, 189 patients were enrolled, with 92 in cisplatin arm and 90 in cetuximab included in the main analysis. There was no difference in the primary endpoint of symptom severity; difference in area under the curve cetuximab-cisplatin was 0.05 (95% confidence interval [CI], –0.19, 0.30), P = .66. The T-score (mean number of ≥grade 3 acute adverse events) was 4.35 (standard deviation 2.48) in the cisplatin arm and 3.82 (standard deviation 1.8) in the cetuximab arm, P = .108. The 3-year failure-free survival rates were 93% (95% CI, 86%-97%) in the cisplatin arm and 80% (95% CI, 70%-87%) in the cetuximab arm (hazard ratio = 3.0 [95% CI, 1.2-7.7]); P = .015. For patients with low-risk HPV-associated oropharyngeal cancer, radiation therapy and cetuximab had inferior failure-free survival without improvement in symptom burden or toxicity compared with radiation therapy and weekly cisplatin. Radiation therapy and cisplatin remain the standard of care.